Sol-gel synthesis of ZnO nanoparticles for optmized photocatalytic degradation of Eriochrome Black T under UV irradiation - Auwal Yusha-Muhammad Sulaiman Darmaa-Kamaluddeen Abubakar Isahb (University of Eloued جامعة الوادي, 2023)
In this work, zinc oxide (ZnO) nanoparticles was synthesized by sol-gel method and characterized using x-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), energy dispersive spectroscopy (EDS) and ultraviolet-visible (UV-Vis) spectrophotometry. The XRD analysis of the as synthesized catalyst revealed a hexagonal wurtzite structure. The average particle size and band gap values were 24.67nm and 3.28eV respectively. The peak observed at 452cm-1 corresponds to Zn-O stretching vibrational band. The effect of operating paramers such as initial concentration of eriochrome black-T (EBT), concentration of catalyst and pH of the solution was optimized using box-benhken design (BBD) and response surface methodology (RSM). The optimum photodegradation efficiency of 96.59% was obtained at 15.00mg of EBT concentration, 0.40g catalyst concentration and initial pH of 9.00. The degradation model was statistically remarkable with p < 0.0001% in which the EBT initial concentration and catalyst concentration were the most significant variables influencing the degradation of EBT over ZnO photocatalyst under UV irradiation
Article
Keywords: Photocatalysis; ZnO; Box-benhken; UV-light; Eriochrome Black T.